"This New Chapter of Life": Content Analysis of Facebook Posts After Traumatic Brachial Plexus Injury. Issue 2 (July 2021) - Zhu, Eric; Rolf, Liz; Smolev, Emma T.; Brogan, David M.; Dy, Christopher J.
Background: After traumatic brachial plexus injuries (BPI), the sudden loss of physical function is often accompanied by psychological distress. Given the complex nature and relative infrequency of the injury, BPI patients will often use online resources for information about their injury as well as emotional support. Questions/Purpose : Recognizing the influence of social media, we sought to search a popular social media platform to identify challenges faced by BPI patients and strategies used to overcome these challenges. Methods : We searched "traumatic brachial plexus injury" on Facebook and selected the 2 most popular BPI support groups. We collected posts regarding traumatic BPI from November 1, 2018 through November 1, 2019. We performed inductive and deductive thematic analysis of the posts to identify recurring topics, knowledge gaps, and peer interaction dynamics. Results : We analyzed 7694 posts from the 2 Facebook support groups. The following themes emerged: (1) BPI patients express discontent regarding the inability to use their arm and the slow or stagnant pace of recovery; (2) BPI patients are frustrated over their inability to retain their preinjury livelihood; and (3) BPI patients emphasize that acceptance and moving on are key components of adjustment to their condition. Some patients described the role of limb amputation in achieving these goals. Conclusions : Our analysis demonstrates the areas in which BPI patients are in need of emotional support. Adjustment to BPI might be facilitated through multidisciplinary care that addresses emotional aspects of recovery and emphasizes self-management skills, in addition to the traditional focus on physical function.